Comparison of Two Methodologies for CD4+T Lymphocytes Relative Counting on Immune Monitoring of Patients with Human Immunodeficiency Virus - Kalva Borato, Danielle Cristyane; Carraro, Emerson; Weber Ribas, Sonia Regina; Kalva-Filho, Carlos Augusto [UNESP]; Rebuglio Vellosa, Jose Carlos (Hindawi Publishing Corporation, 2012)
Considering that counting the percentage of CD4 T lymphocytes can add prognostic information regarding patients infected with HIV, the aim of this study was to evaluate the percentage values of CD4+ T lymphocytes from 81 patients determined by flow cytometry and estimated by flow cytometry in conjunction with a hematology counter. Means were compared through the Student's t-test. Pearson's correlation was determined, and the agreement between results was tested by Bland-Altman. The level of significance was P < 0.05. It was found a significantly higher mean difference between the relative values of CD4+ T lymphocytes to the hematologic counter (P < 0.05), for all strata studied. Positive and significant correlations (P < 0.01) were found between the strata CD4 < 200 cells/mL (r = 0.93), between 200 and 500 cells/mL (r = 0.65), and >500 cells/mL (r = 0.81). The limits of agreement were 1.0 +/- 3.8% for the stratum of CD4 < 200 cells/mL, approximately 2.2 +/- 13.5% for the stratum of CD4 between 200 and 500 cells/mL, and approximately 6.2 +/- 20.4% for the stratum > 500 cells/mL. The differences in the percentages of CD4+ T lymphocytes obtained by different methodologies could lead to conflict when used in clinical decisions related to the treatment and care of people infected with HIV.